1999
DOI: 10.1074/jbc.274.42.30146
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a C-terminal Tail in the Mammalian Gonadotropin-releasing Hormone Receptor Confers Resistance to Agonist-dependent Phosphorylation and Rapid Desensitization

Abstract: The mammalian gonadotropin-releasing hormone receptor (GnRH-R) is, at present, the only G-protein-coupled receptor that activates phospholipase C and lacks a C-terminal tail. We have previously demonstrated that this unique structural feature is associated with resistance to rapid desensitization of phosphoinositide signaling in COS-7 and HEK-293 cells (Heding, A., Vrecl, M., Bogerd, J., McGregor, A., Sellar, R., Taylor, P. L., and Eidne, K. A. (1998) J. Biol. Chem. 273, 11472-11477). Using receptors tagged wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
71
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 44 publications
7
71
2
Order By: Relevance
“…In contrast, another study, which also compared the rates of internalization for the TRHR subtypes in COS-1 cells and more recently in HEK293 cells, reported a different rate for both TRHR1 and TRHR2 (14,52). However, as the rate for TRHR1 internalization obtained by us is in agreement with that previously published by others (20,23,25,26,53,54), we are unable to explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast, another study, which also compared the rates of internalization for the TRHR subtypes in COS-1 cells and more recently in HEK293 cells, reported a different rate for both TRHR1 and TRHR2 (14,52). However, as the rate for TRHR1 internalization obtained by us is in agreement with that previously published by others (20,23,25,26,53,54), we are unable to explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, internalization of catfish GnRH-R is ␤-arrestin-dependent (24), whereas internalization of the human GnRH-R is not (25). Thus non-mammalian GnRH-Rs appear to follow the scheme outlined above for ␤-arrestin-mediated desensitization and internalization (and possible ␤-arrestin-mediated signaling), but this is not the case for the mammalian GnRH-Rs investigated to date (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, all cloned non-mammalian GnRH-Rs possess such tails and, since the serine and threonine residues that are phosphorylated by GRKs are often found within the C-terminal tail, comparative studies have addressed the functional relevance of these structures. These have revealed that mammalian GnRH-Rs do not show rapid homologous desensitization (21)(22), whereas non-mammalian GnRH-Rs do rapidly desensitize (23) and that, although mammalian GnRH-Rs undergo agonist-induced internalization via CCVs, they are internalized much more slowly than nonmammalian GnRH-Rs. Moreover, where investigated, nonmammalian GnRH-Rs show agonist-induced phosphorylation and ␤-arrestin translocation and undergo ␤-arrestin-dependent internalization (24), whereas mammalian GnRH-Rs do not (25).…”
mentioning
confidence: 99%
“…In some GPCRs, these phosphorylation events allow for interaction with ␤-arrestins and subsequent receptor deactivation and internalization (25,26). Consistent with the lack of an extensive C-terminal tail, the GnRHR does not appear to undergo arrestindependent internalization or desensitization (27)(28)(29)(30)(31). In fact, the GnRHR has been considered as a naturally occurring internalization resistant mutant (28).…”
mentioning
confidence: 88%